1996
DOI: 10.1006/viro.1996.0305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Identification of a New Hantavirus Causing Severe Pulmonary Syndrome in Argentina

Abstract: A fatal case of serologically confirmed hantavirus pulmonary syndrome (HPS) was recently reported in southwestern Argentina. Nucleotide sequence analysis of PCR fragments from conserved regions of the S and M genomic segments of the virus, amplified from RNA extracted from autopsy lung and liver tissues, showed the virus (referred as Andes virus) to be novel. Comparisons between Andes virus genome sequences with the corresponding sequences of the more closely related hantaviruses revealed differences at the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
149
0
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(158 citation statements)
references
References 0 publications
1
149
0
8
Order By: Relevance
“…Immunohistochemical analysis for hantaviral antigens was performed by using a cross-reactive monoclonal antibody directed against conserved hantaviral nucleocapsid epitopes (12). Specimens from HPS patients were also examined for viral genetic materials (M and S segment) by nested and heminested RT-PCR from either autopsied tissues or blood clot samples (13,14). Genetic sequencing of RT-PCR products derived from patient samples was also performed.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Immunohistochemical analysis for hantaviral antigens was performed by using a cross-reactive monoclonal antibody directed against conserved hantaviral nucleocapsid epitopes (12). Specimens from HPS patients were also examined for viral genetic materials (M and S segment) by nested and heminested RT-PCR from either autopsied tissues or blood clot samples (13,14). Genetic sequencing of RT-PCR products derived from patient samples was also performed.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…In phylogenetic analysis, all viruses associated with cases of HPS from Argentina [6,19], Chile [20], Paraguay [21] and Uruguay (P. J. Padula, unpublished observations) and sigmodontine-related virus from Bolivia [22,23], clustered together with Andes virus [24] and some North American viruses like Sin Nombre (SN) [2,25], Bayou (BAY) [26] or Black Creek Canal (BCC) [27].…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, the first cases of HPS were recorded and characterized in 1995 in the Southwest (López et al 1996). Nowadays, the occurrence of cases is concentrated in three geographically isolated areas: North (Salta and Jujuy provinces), Center (Buenos Aires, Santa Fe and Entre Ríos provinces), and Southwest (Neuquén and Río Negro provinces).…”
mentioning
confidence: 99%
“…In an extensive study conducted in sites were HPS cases occurred, many sigmodontine species were found infected with hantavirus, with seroprevalences which varied between 1.5 and 10.2%, depending on the area and species (Calderón et al 1999, Cantoni et al 2001. López et al (1996López et al ( , 1997 described the virus associated to HPS cases in Argentina, Andes virus (AND), as a new type of hantavirus. This virus circulates in Argentina, Chile and Uruguay with different lineages that are characteristics of the different areas (Padula et al 2000a).…”
mentioning
confidence: 99%